Preparation and characterization of TiO2-sulfonated polymer embedded polyetherimide membranes for effective desalination application - Thuyavan, Y. Lukka (Elsevier, 2015)
Nanocomposite polyetherimide/TiO2-sulfonated polymer membranes were fabricated by phase inversion process, using Dimethylacetamide as solvent. The sulfonated polymers such as sulfonated poly(ether ether ketone) (SPEEK) and sulfonated polyethersulfone (SPES) self-assemble with TiO2 to form resultant hybrid PEI membranes. Such hybrid membranes were characterized by attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, contact angle, scanning electron microscopy (SEM) and LCR meter. Among these membranes, TiO2-SPEEK incorporated PEI membrane shows a higher flux of 44.75L/m2h and lesser contact angle value of 61.38°. It is observed that such combination improves the membrane surface functionality. In addition, the filtration of three different electrolytes (NaCl, Na2SO4 and MgSO4) with varying concentrations from 50 to 500mg/L on resulted membranes was analyzed. It is inferred that an increasing dielectric constant value increased the salt rejection in such membranes. Also, a higher retention coefficient of 0.72 was observed during filtration of Na2SO4 using PEI/SPEEK/TiO2 membrane. Effects of ground water on flux profile and flux reduction ratio in the fabricated membrane were also analyzed and discussions are provided.